Frequency control for microgrids using enhanced STATCOM and supercapacitor energy storage - Agbedahunsi, Alex Taiwo (2013)
The face of electricity generation, transmission and distribution is changing due to economic, technology and environmental incentives. Recently, interactive and intelligent electricity grid structures which consist of interconnected small/medium sized generators, power electronic technologies and energy storage elements have been developed to address the major shortcomings of the traditional electricity grid structure. Microgrids are key elements of these emerging grid structures. Although microgrids are accepted as possible solutions to power quality and power stability issues in ac power systems, the uncertainty in the ability of microgrids to cope with severe fluctuating load and fault conditions is a major concern in the operation of these new grid structures. This project was aimed at improving frequency control within a microgrid. Four objectives were identified and addressed to meet this aim.